Plasty of the crural septum in two planes: a proposal for the correction of femoral hernia - Ribero, Gustavo; Cimarra, Fernando; Caraballo, Mónica; Cepellini, Raúl (Cirugía del Uruguay, 1997)
The authors pesent the anatomosurgical basis that make possible the development of an original correction technique for crural henia through crural access.